Molecular Docking: A Review Paper (International Journal of Innovative Research in Engineering & Management, 2023)
Molecular docking basically explains about  the orientation of a molecule preferred to the other  molecule in a manner as in when they attach to each other  in order to get a steady complex. By using scoring functions  further the power of alliance or the irrevocable affinity of  the different molecules is predicted by the preferred  orientation of the two molecules. These interactions, which are achieved by molecular docking between important  biological components such as proteins, peptides, nucleic  acid, carbohydrates, and lipids, are crucial in signal  transduction. Further, these interactions between two  molecules which are being performed by the help of  molecular docking also helps in predicting the type of  signals produced. Therefore, molecular docking is helpful  in predicting both strength and type of signals produced by  the molecules. Because of its ability to predict the coupling  compliance of small particle ligands to the appropriate  target restriction site, molecular docking is among the most  often used strategies in structure-based drug design.  Characterization of the coupling conduct assumes a  significant job in discerning structure of medications just as  to clarify crucial biochemical procedures.
Keywords: Docking; Ligand; Molecular; Models; Orientation